Uso de la pasta triple antibiótica en el tratamiento de conductos radiculares” revisión bibliográfica - Yánez Figueroa, Jennifer Lucia (2025)
Triple Antibiotic Paste has been extensively studied as an option for root canal treatment in primary teeth. Objective: To analyze the use of triple antibiotic paste in root canal treatment of primary teeth in order to eliminate or prevent bacterial infection within the root canal system, ensuring complete disinfection and the preservation of the primary tooth during its retention period in the oral cavity. Materials and Methods: An exhaustive search and analysis of the scientific literature was conducted in databases such as PubMed, Web of Science, and Scopus, using search strings with Boolean operators. The article selection process followed PRISMA guidelines, applying inclusion and exclusion criteria to optimize the identification and efficient retrieval of relevant data. Results: A total of 183 articles were collected, and 12 relevant studies were included. The results show that triple antibiotic paste is effective in eradicating endodontic infections in primary teeth, increasing treatment success rates and reducing the recurrence of infections. A positive impact on pulp vitality and root apex formation in immature teeth was observed. Conclusion: Triple antibiotic paste is an effective and safe option for root canal treatment in primary teeth, with additional benefits for pulp vitality preservation and root development. However, the search for alternative materials with lower toxicity remains necessary to improve the safety of endodontic treatment.